2012
DOI: 10.1016/j.prevetmed.2011.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The cost–benefit of biosecurity measures on infectious diseases in the Egyptian household poultry

Abstract: Increased animal intensification presents with increasing risks of animal diseases. The Egyptian household poultry is peculiar in its management style and housing and this present with particular challenges of risk of infection to both the flock and humans. Biosecurity remains one of the most important means of reducing risks of infection in the household poultry, however not much information is available to support its feasibility at the household level of production. In this study financial feasibilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 24 publications
(7 reference statements)
0
38
0
1
Order By: Relevance
“…These findings suggest that small commercial farmers could be motivated to maintain biosecurity with interventions that protect their investment and maintain profitability by keeping their flock safe from diseases they consider harmful through the involvement of local vendors they value. A study in Egypt showed that the benefit–cost ratio for implementing biosecurity measures was 8.45 against HPAI and 4.88 against Newcastle disease for household poultry (Fasina et al 2012). Although the government recommended different biosecurity measures for different commercial poultry sectors, the recommendations mostly included general measures for all farm sizes (Department of Livestock Services 2010), which may not be practical for small farms.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that small commercial farmers could be motivated to maintain biosecurity with interventions that protect their investment and maintain profitability by keeping their flock safe from diseases they consider harmful through the involvement of local vendors they value. A study in Egypt showed that the benefit–cost ratio for implementing biosecurity measures was 8.45 against HPAI and 4.88 against Newcastle disease for household poultry (Fasina et al 2012). Although the government recommended different biosecurity measures for different commercial poultry sectors, the recommendations mostly included general measures for all farm sizes (Department of Livestock Services 2010), which may not be practical for small farms.…”
Section: Discussionmentioning
confidence: 99%
“…Biosecurity has focus on maintaining or improving the health status of animal and preventing the introduction of new disease pathogens by assessing all possible risks to animal health (Satyanarayana et al, 2008;Zavala, 2011;Australian Biosecurity Co-operative Research Centre, 2009;Fraser et al, 2010;Iqbal, 2009;Dorea et al, 2010;Julien and Thomson, 2011;Fasina et al, 2011). Most animal health programs will increase their odds of success (Msoffe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of financial constraints were recognized in implementing these measures in a resource-poor setting. With the exception of one economic model [91], there are virtually no cost-benefit studies using field data. Guidelines have been issued to train farmers on how to reduce contacts with domestic birds and increase biosecurity in backyard flocks [33,69,77,78].…”
Section: Discussionmentioning
confidence: 99%